Psicologia no Brasil: a presença dos Salesianos - Brandão, Iolanda Bezerra dos Santos (2006)
In order to continue the research started during the Masters, this present thesis focuses on the work in psychology done by the Salesianos in Brazil that dates back to 1940, when a group of fathers that belonged to the Congregação Salesiana were sent to Italy to specialize in psychology, particularly in empirical psychology. When they returned to Brazil they developed many activities regarding psychology and funded in some Salesianos Colleges, Psychology Institutes, supported by empirical psychology laboratories, equipped with devices and tests brought from Italy, under the supervision of the father Giacomo Lorenzini